Unusual facial perforation by less lethal munition: Case report (Research, Society and Development, 2021)
Rubber bullets are considered “non-lethal weapons”, however, when they reach the facial region they can leave serious sequelae or even cause death. Such projectiles can reach the facial region, causing bone destruction, neurological and vascular damage, as well as, favoring the development of diseases. The present study aims to report a case of a 32-year-old male patient affected by a rubber bullet-compatible projectile at the time of a police dispersion. The patient attended the emergency service of the Instituto Doutor José Frota - CE, reinforced eyelid ptosis, ecchymosis and periorbital edema of both eyes, being evidenced in the left eye and a cut-contusion wound in the medial corner of the orbit. In the preoperative computed tomography, it was observed: foreign body housed in the blood base - inside the sphenoid sinus. The diagnosis and treatment decision was made by a multidisciplinary team. The patient was submitted to a surgical center under general anesthesia to remove the projectile and use LPR-F. The patient progresses with 03 (three) months of postoperative follow-up, with no signs of infection or outflow of CSF fistula. A search was performed in the literature for articles published in the years between 1975-2017 in English. The penetrating losses caused by a rubber bullet in the face must be treated by a multidisciplinary team in association with complementary exams such as a computed tomography to diagnose and define the treatment with a better prognosis.